Posterior Cruciate Ligament Reconstruction in the Multiple Ligament Injured Knee - Kew, Michelle E.; Miller, Mark D. (The Journal of Knee Surgery, 2020)
Multiligamentous knee injuries are challenging to treat and diagnose. Posterior cruciate ligament (PCL) injuries are commonly found in the constellation of injuries included in a multiligamentous knee injury and are caused by a posteriorly directed force on the proximal tibia with relation to the femoral condyles. A thorough history and physical examination should be performed to evaluate for associated neurovascular injuries and associated ligamentous, chondral, or bony injuries. Nonsurgical management is reserved for patients who are critically ill or have very low activity demands. Surgical reconstruction is recommended for most patients with multiligamentous knee injuries. The PCL reconstruction can be undertaken with several different graft options and reconstruction techniques, including the transtibial, arthroscopic tibial inlay, and open tibial inlay approach. The literature has a paucity of data regarding outcomes among the various reconstructive options, so the optimal surgical technique has not been established.
Keywords: knee; ligamentous injury; ligament reconstruction